Bardet-Biedl Syndrome as a Chaperonopathy: Dissecting the Major Role of Chaperonin-Like BBS Proteins (BBS6-BBS10-BBS12) - Álvarez-Satta, María; Castro-Sánchez, Sheila; Valverde, Diana (Frontiers in Molecular Biosciences, 2017)
Bardet-Biedl syndrome (BBS) is a rare genetic disorder that belongs to the group of ciliopathies, defined as diseases caused by defects in cilia structure and/or function. The six diagnostic features considered for this syndrome include retinal dystrophy, obesity, polydactyly, cognitive impairment and renal and urogenital anomalies. Furthermore, three of the 21 genes currently known to be involved in BBS encode chaperonin-like proteins (MKKS/BBS6, BBS10 and BBS12), so BBS can be also considered a member of the growing group of chaperonopathies. Remarkably, up to 50% of clinically-diagnosed BBS families can harbor disease-causing variants in these three genes, which highlights the importance of chaperone defects as pathogenic factors even for genetically heterogeneous syndromes such as BBS. In addition, it is interesting to note that BBS families with deleterious variants in MKKS/BBS6, BBS10 or BBS12 genes generally display more severe phenotypes than families with changes in other BBS genes. The chaperonin-like BBS proteins have structural homology to the CCT family of group II chaperonins, although they are believed to conserve neither the ATP-dependent folding activity of canonical CCT chaperonins nor the ability to form CCT-like oligomeric complexes. Thus, they play an important role in the initial steps of assembly of the BBSome, which is a multiprotein complex essential for mediating the ciliary trafficking activity. In this review, we present a comprehensive review of those genetic, functional and evolutionary aspects concerning chaperonin-like BBS proteins, trying to provide a new perspective that expands the classical conception of BBS only from a ciliary point of view.